On a class of intermediate local-nonlocal elliptic problems - Alves, Claudianor O.; Corrêa, Francisco Julio S. A.; Chipot, Michel (Topological Methods in Nonlinear Analysis, 2016)
This paper is concerned with the existence of solutions for a class of intermediate local-nonlocal boundary value problems of the following type: $$ -\rom{div} \bigg[a\bigg(\fint_{\Omega (x,r)}u(y)dy\bigg) abla u\bigg] = f(x,u, abla u ) \quad \mbox{in } \Omega, \ u\in H_{0}^{1}(\Omega ), \leqno{(\rom{IP})} $$% where $\Omega$ is a bounded domain of $\mathbb{R}^{N}$, $a\colon\mathbb{R} \rightarrow \mathbb{R}$ is a continuous function, $f\colon \Omega \times \mathbb{R} \times \mathbb{R}^{N}$ is a given function, $r> 0$ is a fixed number, $\Omega (x,r)=\Omega \cap B(x,r)$, where $B(x,r)=\{ y\in \mathbb{R}^{N}: |y-x|< r\}$. Here $|\cdot |$ is the Euclidian norm, $$ \fint_{\Omega (x,r)}u(y)dy=\frac{1}{\rom{meas}\hspace{.06em}(\Omega (x,r))}\int_{\Omega (x,r)}u(y)dy $$ and $\rom{meas}\hspace{.06em}(X)$ denotes the Lebesgue measure of a measurable set $X\subset \mathbb{R}^{N}$.